2020
DOI: 10.3847/1538-4357/ab5360
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of S8 in Interstellar Ices: The Effects of Cosmic-Ray-driven Radiation Chemistry and Nondiffusive Bulk Reactions

Abstract: In this work, we reexamine sulfur chemistry occurring on and in the ice mantles of interstellar dust grains, and report the effects of two new modifications to standard astrochemical models; namely, (a) the incorporation of cosmic ray-driven radiation Corresponding author: Christopher N. Shingledecker cns@mpe.mpg.de Shingledecker et al. et al. (2016). In that work, the authors concluded that this S 2 likely formed in the pre-solar nebula via the radiolysis of species such as H 2 S. In an attempt to improve how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 85 publications
2
82
0
Order By: Relevance
“…First, radicals and reactive species produced through the radiolysis of molecules by GCRs can diffuse before reacting with neighboring species. However, recent simulations of interstellar ice chemistry incorporating cosmic-ray-driven radiation chemistry indicate that radicals and reactive species quickly react with neighboring species in the ice (Shingledecker et al 2019(Shingledecker et al , 2020, in agreement with experiments that provided no evidence for true bulk diffusion (Ghesquière et al 2018). Then, once secondary species are formed, they can diffuse within the nucleus.…”
Section: Impact Of Gcr On Chemical Compositionsupporting
confidence: 64%
“…First, radicals and reactive species produced through the radiolysis of molecules by GCRs can diffuse before reacting with neighboring species. However, recent simulations of interstellar ice chemistry incorporating cosmic-ray-driven radiation chemistry indicate that radicals and reactive species quickly react with neighboring species in the ice (Shingledecker et al 2019(Shingledecker et al , 2020, in agreement with experiments that provided no evidence for true bulk diffusion (Ghesquière et al 2018). Then, once secondary species are formed, they can diffuse within the nucleus.…”
Section: Impact Of Gcr On Chemical Compositionsupporting
confidence: 64%
“…According to modeling results of Laas & Caselli (2019), the principal sulfur-bearing species in the ice at advanced chemical stages are SO, OCS, HSO, and CS. Also, pure-sulfur molecules, in particular S 8 , have been suggested to be abundant on grains (Shingledecker et al 2020). Methanol and sulfur monoxide are not directly related.…”
Section: Origin Of Gaseous Methanol In H-mm1mentioning
confidence: 99%
“…In non-astrophysical solids, it is well known that diffusion along crystallite grain boundaries is generally enhanced compared to the crystal or mineral equivalent. 32,33 Experimental data 34 and astrochemical models 35,36 have suggested that structural diffusion within the bulk ice may actually enhance reactivity. This would suggest that CO 2 diffusion along the crystallite grain boundaries was higher in the NH 3 -rich mixtures which may also have increased reactivity.…”
Section: Discussionmentioning
confidence: 99%